Pathophysiology and Immune Dysfunction in Endometriosis. (12th July 2015) - Ahn, Soo Hyun; Monsanto, Stephany P.; Miller, Caragh; Singh, Sukhbir S.; Thomas, Richard; Tayade, Chandrakant
Abstract : Endometriosis is an estrogen-dependent, chronic, proinflammatory disease prevalent in 10% of women of reproductive age worldwide. Characterized by the growth of endometrium-like tissue in aberrant locations outside of the uterus, it is responsible for symptoms including chronic pelvic pain, dysmenorrhea, and subfertility that degrade quality of life of women significantly. In Canada, direct and indirect economic cost of endometriosis amounts to 1.8 billion dollars, and this is elevated to 20 billion dollars in the United States. Despite decades of research, the etiology and pathophysiology of endometriosis still remain to be elucidated. This review aims to bring together the current understanding regarding the pathogenesis of endometriosis with specific focus on mechanisms behind vascularization of the lesions and the contribution of immune factors in facilitating lesion establishment and development. The role of hormones, immune cells, and cytokine signaling is highlighted, in addition to discussing the current pharmaceutical options available for management of pain symptoms in women with endometriosis.